Public relations in a time of turbulence: A study on Turkish PR firms - Uzunoğlu, Ebru; Onat, Ferah (Journal of Human Sciences, 2012)
2008 global economic crisis affected many companies. In order to survive and to become more competitive in today’s turbulent business world, companies took drastic actions to gain cost reduction from every part of their business. Turkey, having been experienced a bigger crisis in 2001 and developed many models to manage the situation until 2008, is accepted as being more precautious than other countries. Still, Turkish public relations (PR) firms have been subjected to many changes, particularly advances in communication technologies, which have forced PR firms to restructure their organizations and adapt to new business models. The main purpose of our research is to gain insight on how Turkish PR firms adapted to the time of turbulence. Our research is based on qualitative data obtained from leading PR firms that are the members of ICCO representative IDA (Communication Consultancy Companies Association) in Turkey.